Towards semi-inclusive deep inelastic scattering at next-to-next-to-leading order - Anderle, Daniele (2017)
In this paper, we compute the first set of O(αs2) corrections to semi-inclusive deep inelastic scattering structure functions. We start by studying the impact of the contribution of the partonic subprocesses that open at this order for the longitudinal structure function. We perform the full calculation analytically, and obtain the expression of the factorized cross section at this order. Special care is given to the study of their flavor decomposition structure. We analyze the phenomenological effect of the corrections finding that, even though expected to be small a priori, it turns out to be sizable with respect to the previous order known, calling for a full next-to-next-to-leading order calculation.